Analysing the importance of Malaysian gastronomic tourism campaigns and tour packages in attracting tourists to visit / Mohd Nor Ahmar Mohd Sanip, Ramlee Mustapha and Suriani Mohamed - Mohd Sanip, Mohd Nor Ahmar; Mustapha, Ramlee; Mohamed, Suriani (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
A recent trend that showcases gastronomy as the main tourist product has shown the importance for travel and tour operators; hoteliers; and local authorities to develop effective strategies to attract local as well as international tourists to visit Malaysia. Described as one of the jewels for gastronomic tourism in Southeast Asia, Malaysia is well-known for its rich food heritage with diverse and vibrant eating surroundings. As the competition to attract tourists increases in the Asian region, it is worth putting forward Malaysian gastronomy as a valuable source of attraction. The task of attracting tourists lies in the gastronomic tourism campaigns and tour packages offered by hoteliers, travel agencies, and the respective bodies of authority. This study focuses on the antecedents of gastronomic tourism marketing in a destination, in particular the analysis of gastronomic tourism campaigns and tour packages which varied according to the hoteliers; travel and tour operators; and local authorities who had planned them. The qualitative content analysis approach was used on selected Malaysian cuisine marketing collateral— including travel guides and webpages—to extract relevant data for this study. By looking at the tourists’ quest for authentic local cuisines and experiences, there is a need to recognise the role of effective marketing tools to attract tourists—both local and international— to favour Malaysian gastronomic products. Gastronomic packages and campaigns which emphasise local ethnic cuisine experiences and activities should be aggressively promoted by all relevant parties. Additionally, the local food scene and culture may also be introduced as another attraction for future visits.